Perpendicular magnetic anisotropy induced by La2/3Sr1/3MnO3–YBaCo2O5+δ interlayer coupling. (17th February 2021) - Han, Furong; Chen, Xiaobing; Wang, Jianlin; Huang, Xudan; Zhang, Jine; Song, Jinghua; Liu, Banggui; Chen, Yuansha; Bai, Xuedong; Hu, Fengxia; Shen, Baogen; Sun, Jirong
Abstract: Heterostructure with a symmetry-mismatched interface provides a promising playground for the exploration of emergent phenomena. Herein, we report a systematic investigation on La2/3 Sr1/3 MnO3 /YBaCo2 O5+ δ (LSMO/YBCO) grown on SrTiO3, a heterostructure formed by perovskite oxides of different symmetry. A high-resolution lattice image shows the formation of high-quality perovskite LSMO and A-site cation-ordered oxygen-deficient double perovskite YBCO, without any signatures of atomic reconfiguration at the interface. Surprisingly, the YBCO-buffered LSMO exhibits perpendicular magnetic anisotropy (PMA), though bare LSMO film is in-plane anisotropic. The PMA is robust, appearing even when the thickness of YBCO is only one unit cell. The typical anisotropy constant is ∼4 × 10 6 erg cm −3 . X-ray absorption spectroscopy analysis reveals a preferential occupation of the d 3 z 2 − r 2 orbital compared with d x 2 − y 2, which is confirmed by density functional theory calculations. This orbital reconstruction accounts for the PMA. The formation of a covalent bond between Mn and Co caged by different oxygen polyhedrons, an octahedron and a square pyramid, respectively, stabilizes the orbital reconstruction, resulting in anomalous spin orientation.